Application of ultrasonography in sports: A systematic review - Błaszków, Krzysztof; Szydłowska, Sara; Elias, Jagoda; Biesiada, Wiktor; Zubiak, Marlena; Kaźmierczak, Dominika (Journal of Education, Health and Sport, 2025)
Ultrasonography (USG) plays a crucial role in the diagnosis and monitoring of sports injuries. Due to its accessibility, low invasiveness, and the ability to perform dynamic real-time examinations, USG is widely used in the assessment of muscle, tendon, ligament, and joint injuries. Modern technologies, such as elastography and power Doppler, enable precise analysis of the biomechanical properties of tissues, which facilitates the planning of therapy and rehabilitation. The aim of this study is to conduct a systematic review of the literature on the use of ultrasonography in sports, with a particular focus on its role in injury diagnosis and the optimization of treatment and recovery processes for athletes.